Menuju Keluarga yang Harmonis: Manajemen Konflik Politik dalam Keluarga di Tengah Perbedaan Pilihan Politik - Sugitanata, Arif; Ridwan, Muannif (Jurnal Indragiri Penelitian Multidisiplin, 2024)
Different political choices within households create interesting dynamics as well as potential conflicts. This phenomenon reflects the diversity of views and values within families. This research utilizes primary sources such as books, journals, and websites, covering diverse perspectives. Qualitative research type and descriptive-analytic method are used to describe and analyze the conflict. Two theoretical frameworks, social conflict and conflict management, were used for a more comprehensive understanding. The results show that family harmony is considered important as it contributes to the well-being of family members. Political conflicts in the family, especially related to the presidential and vice presidential elections, are complex and influenced by social media, identity, and emotional aspects. Solutions involve understanding, open communication, information checking, the value of tolerance, and an agreement to maintain privacy in political discussions. The role of parents is crucial in modeling good behavior. Analysis based on social conflict theory highlights the role of social media, identity and emotions in conflict. Identification of differences and poor communication exacerbate tensions. Conflict management provides guidance on solutions and steps to manage differences in political views in the family. Overall, this study shows that social conflict management can be applied in a family context to maintain harmony amidst differences in political choices. The proposed solutions involve understanding, open communication, information checking, the value of tolerance, and the role of parents as positive behavior models. Thus, family harmony can be maintained, creating a healthy and loving family environment.